350 = 2 ⋅ 52 ⋅ 7
180 = 22 ⋅ 32 ⋅ 5 gcd(350, 180) = 2 ⋅ 5
lcm(350, 180) = 22 ⋅ 32 ⋅ 52 ⋅ 7
A = {2, 3, 5, 9, 15}Fill in the table below indicating the set that the expression evaluates to.
B = {1, 3, 6, 8, 15}
C = {1, 2, 5, 7, 11}
Expression | Value |
---|---|
(A ∪ B) ∩ C | {1, 2, 5} |
(A ∩ C) ∪ B | {1, 2, 3, 5, 6, 8, 15} |
A ∩ B ∩ | {4, 7, 10, 11, 12, 13, 14} |
B ∪ C | {4, 9, 10, 12, 13, 14} |
N = set of natural numbers (0, 1, ...)Fill in the table below indicating "yes" or "no" whether the given function is onto and one-to-one for the given mapping.
Z = set of integers
Z+ = set of positive integers (1, 2, ...)
R = set of reals
Function | Mapping | Onto? | One-to-One? |
---|---|---|---|
f(x) = (x - 1)2 | Z+ → N | no | yes |
f(x) = (x - 1)2 | N → N | no | no |
f(x) = 2x - 1 | Z → Z | no | yes |
f(x) = 2x - 1 | R → R | yes | yes |
Animal(x) means that x is an animal
Plant(x) means that x is a plant
Furry(x) means that x is furry
Eats(x, y) means that x eats y
For the first three problems below, translate the given sentence into predicate logic using quantifiers when appropriate. No negation should appear in front of a quantifier or in front of a parenthesized expression.
(5 points) Some furry animal eats at least one furry plant.
∃x(Furry(x) ∧ Animal(x) ∧ ∃y(Eats(x, y) ∧ Furry(y) ∧ Plant(y)))
(5 points) Any plant that eats an animal is furry.
∀x(Plant(x) ∧ ∃y(Eats(x, y) ∧ Animal(y)) → Furry(x))
∀x∀y(Plant(x) ∧ Eats(x, y) ∧ Animal(y) → Furry(x))
(5 points) Some animal eats exactly one plant.
∃x (Animal(x) ∧ ∃y(Eats(x, y) ∧ Plant(y) ∧ ∀z(Eats(x, z) ∧ Plant(z) → z = y)))(5 points) Translate the following predicate into English:
∃x (Animal(x) ∧ ∃y(Eats(x, y) ∧ Plant(y) ∧ ∀z(Eats(x, z) → z = y ∨ ¬Plant(z))))
∀x (∃y (Furry(y) ∧ Animal(y) ∧ Eats(y, x)) → (¬Furry(x) ∧ Animal(x)))
Everything that is eaten by a furry animal is a non-furry animal.
Furry animals eat only non-furry animals.
(4 points) Chip is ill.
no (cannot be concluded)
(4 points) Sam is not a patient of Dr. Smith.
yes by 6, 3
(4 points) Mary is a patient of Dr. Jones.
yes by 1, 5, 2
(4 points) Sam has been admitted to the hospital.
no (cannot be concluded)
(4 points) Mary is ill.
yes by 1, 5, 7
We need to prove that:a2 + b2 odd → a + b odd for integers a, bWe can use an indirect proof. Assume that a + b is not odd, which means it is even. Then:a + b = 2k for some integer k
(a + b)2 = (2k)2
a2 + 2ab + b2 = 4k2
a2 + b2 = 4k2 - 2ab
a2 + b2 = 2(2k2 - ab)
Thus, a2 + b2 is even, which means it is not odd. This completes the proof.- Proofs (10 points). Prove that the square of an integer n is 4 more than a multiple of 8 if and only if the square of 5n is 4 more than a multiple of 8. Be sure to indicate the proof technique you are using to solve this problem.
This is an equivalence proof that requires proving in both directions. First we need to prove that:n2 ≡ 4 (mod 8) → (5n)2 ≡ 4 (mod 8)We can prove this directly:n2 = 8k + 4 for some integer k
(5n)2 = 25 n2
= 25 (8k + 4)
= 200k + 100
= 8 (25k + 12) + 4
qedNext we need to prove that:(5n)2 ≡ 4 (mod 8) → n2 ≡ 4 (mod 8)We can prove this directly:(5n)2 = 8k + 4 for some integer k
25n2 = 8k + 4
n2 = 8k + 4 - 24n2
= 8(k - 3n2) + 4
qed- Induction (20 points). Prove using mathematical induction that:
1 + 5 + 52 + 53 + ... + 5n = (5n + 1 - 1)/4Provide a formal definition for the overall proposition being proved (P(n)) using summation notation and indicate the domain for n. Then provide an inductive proof, clearly indicating where you are applying the inductive hypothesis.
Let P(n) be the statement that:We can prove that P(n) holds for n ∈ N using induction.
n
∑
i = 05i = (5n + 1 - 1) / 4 We first prove P(0):
1 = 4 / 4 = (5 - 1) / 4 = (50 + 1 - 1) / 4Then we assume P(k) for some k ∈ N:And we prove P(k + 1):
k
∑
i = 05i = (5k + 1 - 1) / 4
k + 1
∑
i = 05i = (5k + 2 - 1) / 4
k + 1
∑
i = 05i = (by inductive hypothesis)
k
∑
i = 05i + 5k + 1
= (5k + 1 - 1) / 4 + 5k + 1=
= (5k + 1 - 1) / 4 + 4 ⋅ 5k + 1 / 4 =
= (5k + 1 - 1 + 4 ⋅ 5k + 1) / 4 =
= (5 ⋅ 5k + 1 - 1) / 4=
= (5k + 2 - 1) / 4
Therefore P(n) holds for all n ∈ N.